'Go! You are Free!': rentier politics and the gift logic of the royal pardon in Morocco. Issue 6 (2nd November 2022) - El Maarouf, Moulay Driss; Belghazi, Taieb
ABSTRACT: This paper discusses royal pardons and other patronal graces in Morocco as forms of gifting that borrow their logic from Islamic teachings, and protocols binding ar-rā'I (ruler) and ar-ri'āya (subjects). The moment they begin to engage mixed feelings and analyses from politicians, activists, academics, and the general public they give rise to stormy debates, with as of yet unsettled disputes in the thick of social and political tensions in Morocco (from the post-2011 uprisings to the recent al-hirak of El Huceima, to other instances of social unrest (boycotts of consumables, struggles over human rights infringements)). As we posit the debate on rentier economy and politics in the hub of existing theoretical insights on gift-giving, we launch the particularities, subtleties, and dualities of the gift in general as both desirable and undesirable, pure and impure, honouring and humiliating, and the royal gift in particular as a neopatrimonialist act that hinges on referentiality and preferentiality. We draw on examples of potential royal grace receivers (classic criminals, political activists, Rif hirakists, amateur gift hunters, and professional smayria (professional hunters of the royal gift)) as touchstones for rethinking how patronal gifts are sent (as envois), received and lost midway. In the end, we conclude that gifting, far from being about sharing what one has, is about fighting with what one has.